Implementation of Standardized Nursing Language (SNL) in Nursing Documentation: A Scoping Review - Salsabila Fiqrotu Tsauroh; Ariani Arista Putri Pertiwi; Widyawati; Silvia Tri Wahyu Christaputri; Sihqina Ramadhani Selwis Raistanti (Universitas STRADA Indonesia, 2026)
Background: Nurses play a crucial role in improving the quality of care through standardized nursing practices. Standardized Nursing Language (SNL) provides as structured and systematic approach to articulating nursing care, facilitating accurate communication and promoting consistency in nursing documentation. Purpose: This scoping review aimed to identify the implementation of SNL in nursing documentation. Methods: A scoping review was conducted using four electronic databases: Garuda, PubMed, ScienceDirect, and Wiley. Eligible studies full text-original articles published in English or Indonesian between 2020 and August 2025 that examined SNL implementation in documentation within healthcare settings. Studies conducted in educational contexts, case reports, editorial commentaries, conference proceedings, and study protocols, were excluded. Results: Across the 10 included studies, SNL implementation was associated with improvements nursing documentation quality. Five studies (50%) reported improved documentation accuracy and readability, while five (50%) reported more appropriate nursing diagnoses and interventions. The main implementation barriers were inadequate EHR support, limited nurses’ familiarity with SNL, and lack of standardized documentation formats, each reported in five studies (50%). Conclusion: SNL implementation is associated with improved quality and consistency of nursing documentation. Further research using implementation science frameworks is warranted to systematically examine context specific barriers and facilitators of SNL implementation.